2004
DOI: 10.1002/ana.20134
|View full text |Cite
|
Sign up to set email alerts
|

Alternating hemiplegia of childhood or familial hemiplegic migraine?: A novel ATP1A2 mutation

Abstract: Alternating hemiplegia of childhood (AHC) is typically distinguished from familial hemiplegic migraine (FHM) by infantile onset of the characteristic symptoms and high prevalence of associated neurological deficits that become increasingly obvious with age. Expansion of the clinical spectrum in FHM recently has begun to blur the distinction between these disorders. We report a novel ATP1A2 mutation in a kindred with features that bridge the phenotypic spectrum between AHC and FHM syndromes, supporting a possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
103
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 8 publications
4
103
0
2
Order By: Relevance
“…2,7 However, the ATP1A2 mutation was never found in sporadic AHC patients as reported here and by others. 2,7,8 The genetic studies are still ongoing and new hypothesis being are tested. 9 A genetic mechanism should not be excluded for AHC.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…2,7 However, the ATP1A2 mutation was never found in sporadic AHC patients as reported here and by others. 2,7,8 The genetic studies are still ongoing and new hypothesis being are tested. 9 A genetic mechanism should not be excluded for AHC.…”
supporting
confidence: 56%
“…[3][4][5][6] Metabolic studies in Aldh5a1 -⁄ -murine embryos have revealed significant increases in both GABA and GHB as early as day 10 of embryo life, which is of interest since GABA is excitatory during development and might predispose neural circuity to a hyperexcitatory state. 7 GHB also has its own receptor systems, and its accumulation may increase GABA secondarily while exacerbating the effects of GABA on different receptors. 8 Recently, GABA(A) and GABA(B) receptor abnormalities have been suggested in SSADH-deficient patients through studies employing [11C]flumazenil binding and transcranial magnetic stimulation.…”
mentioning
confidence: 99%
“…families with features that bridge the clinical spectrum between FHM and alternating hemiplegia of childhood (AHC), a rare syndrome characterized by early onset of episodic hemiplegia or quadriplegia with autonomic disturbances, movement disorders, and progressive cognitive impairment. 71,72 The Na ϩ ,K ϩ -ATPase pumps generate the ion gradients that maintain resting membrane potential and cell volume and provide the driving force for nutrient and neurotransmitter uptake. Glial and neuronal Na ϩ ,K ϩ -ATPases play an important role in clearance of K ϩ from the extracellular space during neuronal activity 73,74 and are fundamental also for the clearance of released glutamate from the synaptic cleft, because active transport of glutamate into astrocytes and neurons is driven by both Na ϩ and K ϩ gradients.…”
Section: Figmentioning
confidence: 99%
“…6,7 La enfermedad se caracteriza por episodios repetidos de hemiplejía que pueden durar desde algunos minutos hasta varios días; pudiendo existir períodos prolongados sin sintomatología antes de un nuevo episodio. 3 Es habitual la existencia de un retraso inespecífico del desarrollo previo al inicio de los síntomas.…”
Section: Discussionunclassified